Meeting the needs while keeping the source-blood inventory management - Makarovska Bojadzieva, Tatjana; Todorovska, Elizabeta; Arsova, Slavica (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University in Skopje, R.N.Macedonia, 2020)
Background. Blood inventory management is the critical step between the blood supply and blood transfusion. Its main role is to keep the balance between shortage and wastage of blood. Evaluation of our current blood supply and inventory management with an intention to identify the weak points and to propose models to establish best practices that will ensure optimal blood supply with minimal wastage of blood. Material and Methods. We evaluated data concerning the number of whole blood units collected, the number and ABO/D phenotype of the produced, issued and expired blood components (BC), using the donor information system. Results. The linear trend of produced and issued BC shows an increment while the trend of expired BC shows a decrement over the period of 12 months in 2019. The overall rate of produced, issued and expired units is 126, 120 and 6 RBC/day and 78, 67 and 11 PLT/day. The expired RhD negative RBC (25%) and PLT (33%) are significantly greater in comparison to the produced and issued, being 2 times greater for the RBC and 3 times greater for the PLT. The expired AB RBC (16%) and PLT (27%) are significantly higher in comparison to the produced (8.2%) and issued (7.3%) RBC, as well as to the produced (5.7%) and issued (7.3%) PLT. From the total number of expired O RBC (688) and PLT (710), 28% and up to 50% are RhD negative respectively. From the total number of expired AB RBC (340) and PLT (1075), 26.5% and 22% are RhD negative respectively. The ,,universal” O negative RBC and AB negative PLT expire in significantly greater proportion than the produced and issued BC of the same blood type. Conclusion. Blood transfusion experts should work together with the clinicians and the hospitals in setting the indicators for monitoring the blood inventory management in order to minimise shortage and outdating of blood and to meet the patients’ needs for transfusion.
Keywords: blood inventory management; universal red blood cell; expiry rate